Pengaruh Working Capital Turn Over Ratio Dan Current Ratio Terhadap Profitabilitas (Studi Kasus Pada PT. Gudang Garam Tbk Di Bursa Efek Periode 2011 – 2018) - Minsyah Fuadi; Ahmadi Aidi (Neraca : Jurnal Akuntansi Terapan, 2019)
The purpose of the research is to examine the influence of Working Capital Turn Over Ratio and Current Ratio on Profitability by using a measure of Return In Investment. Sampling from this study was taken from the financial statements of PT. Gudang Garam Tbk in the 2011-2018 period from the Indonesia Stock Exchange and data processed using the SPSS version 24 programs.The results of this study indicate that Working Capital Turn Over Ratio has a positive and significant effect on Return In Investments based on the results of the t test obtained Working Capital Turn Over Ratio has a tcount of 6.240 greater than the value of t-table which is 2.051. While the Current Ratio has a negative and opposite effect on the Return In Investment, with a t-count of -3,395 greater than the value of t-table that is 2,051. As the simultaneous Working Capital Turn Over and Current Ratio has an effect on Return In Investments with a significant 0,000 smaller than alpha (α) = 0.05.